An analysis of the relative effects of VKORC1 and CYP2C9 variants on anticoagulation related outcomes in warfarin-treated patients - Meckley, Lisa M.; Wittkowsky, Ann K.; Rieder, Mark J.; Rettie, Allan E.; Veenstra, David L. (Thrombosis and Haemostasis, 2008)
The objective of this study was to assess the relative influence of VKORC1 and CYP2C9 genetic variants on several clinical outcomes related to warfarin treatment. We conducted a retrospective cohort analysis of 172 anticoagulation clinic patients followed from warfarin initiation. We assessed the following clinical outcomes: time to stable dose; time in, above, and below therapeutic range; the probability of overanticoagulation (international normalized ratio [INR] >5); frequency of anticoagulation clinic visits; and the contribution of genetics to maintenance dose. Patients with CYP2C9 variants, compared to those without, achieved stable dose 48% later (p<0.01),spent a higher proportion of time above range in the first month of therapy (14% vs. 25%, p=0.07), and had a higher odds ratio (OR) of an INR >5 (OR: 4.15, p=0.03). In contrast, the only statistically significant effect withVKORC1 was a higher odds of an INR >5 (OR: 4.47,p=0.03) for patients homozygous for theVKORC1 low-dose haplotype (AA) compared to heterozygotes. We did not detect an influence of CYP2C9 norVKORC1 on the frequency of clinic visits. CYP2C9 alone,VKORC1 alone, and a combination of genetic and clinical factors explained 12%, 27%, and 50%,respectively, of the variation in warfarin maintenance dose. In conclusion, genetic variation in VKORC1 appears to have a different influence than CYP2C9 on anticoagulation-related outcomes such as bleeding events and time in therapeutic range. This difference may be due, in part, to pharmacokinetics factors (e.g. drug half-life), which are influenced primarily by CYP2C9; these findings should be confirmed in additional studies.
Keywords: Anticoagulation; pharmacogenetics; pharmacogenomics